2014
DOI: 10.2139/ssrn.2414473
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Biofuels, Economic and Financial Factors on Daily Returns of Commodity Futures Prices

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…On the contrary, there is some case studies show that the introduction of stock index futures to increase the volatil ity of the spot market. Algieri (2014) research S&P500 index of the spot found after the introduction of index futures [6], stock volatility, mainly because foreign investors probably competing holdings of US stocks and index funds. Antoniou (2005) through the FTSE100 index futures research [7], that futures markets have increased volatility in the spot market because the stock index futures will find new information itself, the impact of the spot market, thereby improving the flow of information in the spot market rate.…”
Section: Stock Index Futuresmentioning
confidence: 99%
“…On the contrary, there is some case studies show that the introduction of stock index futures to increase the volatil ity of the spot market. Algieri (2014) research S&P500 index of the spot found after the introduction of index futures [6], stock volatility, mainly because foreign investors probably competing holdings of US stocks and index funds. Antoniou (2005) through the FTSE100 index futures research [7], that futures markets have increased volatility in the spot market because the stock index futures will find new information itself, the impact of the spot market, thereby improving the flow of information in the spot market rate.…”
Section: Stock Index Futuresmentioning
confidence: 99%
“…Fluctuations in the range of normal range is conducive to the active market, so that the market can continue to carry out, but too frequent fluctuations in the market will increase the risk of investors to judge, is not conducive to the good operation of the market [1]. China's stock market belongs to the emerging market range, has been China's stock market volatility and the fluctuation characteristic of high risk is also very obvious, often appear the phenomenon of big ups and downs [2][3]. All of these are the most representative characteristics of the stock market of our country.…”
Section: Introductionmentioning
confidence: 99%